1980
DOI: 10.1021/np50011a008
|View full text |Cite
|
Sign up to set email alerts
|

Uterotonic Effect of Evodia rutaecarpa Alkaloids

Abstract: Rutaecarpine (1) and dehydroevodiamine (2) were isolated from the unripe fruit of Evodia rutaecarpa. In vitro uterotonic assay on rat uterus showed both alkaloids to be active. Dehydroevodiamine was further shown to be active in the in vivo uterotonic assay using rats as the animal model. Reference evodiamine hydrochloride (3) was also evaluated and found to be devoid of uterontonic activity at the doses administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 11 publications
0
33
0
1
Order By: Relevance
“…The role of EVO in the inhibition of tumor cell proliferation has been well-documented in a number of studies (13)(14)(15)(16)(17)(18)(19)(20), while our knowledge of the antitumor effects of EVO on OS cells remains rather sparse. To the best of our knowledge, this is the first study to explore whether EVO possesses anticancer activities in OS cells, and the possible molecular mechanism involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of EVO in the inhibition of tumor cell proliferation has been well-documented in a number of studies (13)(14)(15)(16)(17)(18)(19)(20), while our knowledge of the antitumor effects of EVO on OS cells remains rather sparse. To the best of our knowledge, this is the first study to explore whether EVO possesses anticancer activities in OS cells, and the possible molecular mechanism involved.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, EVO was found to strongly inhibit tumor progression by reducing the proliferation rate and inducing apoptosis in a variety of tumor cells (13)(14)(15)(16)(17)(18)(19)(20). A series of analyses attempted to explain the underlying molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated whether rutaecarpine affects NF-B activation. The compound was isolated as previously described (59). KBM-5 cells were treated with rutaecarpine plus evodiamine and then with TNF.…”
Section: Evodiamine Represses Tnf-induced Nf-b-dependent Genementioning
confidence: 99%
“…Evodiamine has been shown to have various effects on biological processes, such as testosterone [28] and catecholamine secretion [29] , as well as vasodilative [30] , anti-nociceptive [31] , obesity [20] , and thermoregulatory and uterotonic effects [32] . Evodiamine has anti-tumor potential through its ability to inhibit proliferation, induce apoptosis and reduce invasion and metastasis of a wide variety of tumor cells, including breast cancer, prostate cancer, leukemic T-lymphocyte, melanoma, cervical cancer, colon cancer and lung cancer cells [33] .…”
Section: Discussionmentioning
confidence: 99%